Comparison of analgesic effect of preoperative intravenous paracetamol v/s ketorolac in laparoscopic cholecystectomy under general anesthesia - Dr. Budhram Rajoria; Dr. Mahipal Singh Dhaka; Dr. Manisha Malik; Dr. Chetali Das (Journal of Applied Pharmaceutical Research, 2023)
Background: Preemptive analgesia is pain control before inciting a noxious stimulus. Upper abdominal and shoulder tip pain after laparoscopy is probably caused by gas retained in the peritoneal cavity. Pain relievers were given before the incision. Aim: The study was planned to compare the Analgesic effect of pre-operative intravenous Paracetamol versus Ketorolac in laparoscopic cholecystectomy under general anesthesia. The difference in the need for first rescue analgesia and total dose of rescue analgesics in 24 hours postoperative period in both groups was assessed. Methods: This Hospital Based Double Blinded Randomized Interventional Study was carried out in ASA I and II, aged 18 to 60 years in patients undergoing elective laparoscopic cholecystectomy under general anesthesia. Group A received an Intravenous infusion of paracetamol 1gm (100ml) and Group B received an intravenous infusion of ketorolac 30mg (1ml) diluted in 99 ml 0.9% normal saline. In both groups, analgesic was given over a period of 30 minutes, 30 min before induction of general anesthesia. The chi-square test and Student’s t-test were used for the statistical analysis. Results: The time for the demand of the first rescue analgesia was219±81.0 min in group A and 350±175.1min in group B, with a p-value < 0.001. The demand for rescue analgesics was more in Group A in contrast to Group B. Conclusion: We concluded with our study, pre-emptive analgesia with 30mg ketorolac is better than 1 gm paracetamol. The time for rescue analgesia is prolonged, the number of rescue analgesics demanded is reduced, VAS score was significantly lower when ketorolac was used.